1973
DOI: 10.1152/ajplegacy.1973.224.2.399
|View full text |Cite
|
Sign up to set email alerts
|

Contraluminal serum albumin uptake in isolated perfused renal tubules

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…67,73,74 In addition, the rate of apical endocytosis is many times that of basolateral endocytosis in vivo, but the two are equivalent in cell culture. 67,74,75 Therefore, one must not overinterpret cell culture data. Finally, intravenously injected albumin remains intact within the serum and is partially catabolized within PTCs.…”
Section: Endocytosis By the Ptmentioning
confidence: 99%
“…67,73,74 In addition, the rate of apical endocytosis is many times that of basolateral endocytosis in vivo, but the two are equivalent in cell culture. 67,74,75 Therefore, one must not overinterpret cell culture data. Finally, intravenously injected albumin remains intact within the serum and is partially catabolized within PTCs.…”
Section: Endocytosis By the Ptmentioning
confidence: 99%
“…5,6) Accordingly, we suggested that the high urinary albumin excretion in rats with high P intake may arise from diminished proximal tubular function, 5,6) because most albumin reabsorption is in the proximal tubules. 14) That is, proximal tubular function is an important factor in the change in urinary albumin excretion in rats given high-P feed.…”
mentioning
confidence: 99%
“…Furthermore, the increase in urinary albumin excretion may be related to the proximal tubular function, since albumin reabsorption occurs mainly in the proximal tubules. 18) This study demonstrates that renal tubular injury was induced in rats fed the Mg-deˆcient diet. The results suggest that the renal tubular injury induces diminished proximal tubular function, and diminished proximal tubular function leads to an obstruction of proximal tubular albumin reabsorption.…”
Section: Kidney Function In Magnesium Deˆcient Ratsmentioning
confidence: 71%